(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
Language acquisition is one of the most significant achievements of early childhood. The condition for understanding and comprehension is the embeddedness of language in a community. Pedagogical communication in crèches is tied to educational situations but is influenced by the external and internal environment of the crèche. The present research aimed to review the qualitative aspects of communication between children and caregivers based on the evaluation and observation of questionnaire responses. We focused on the presence of quality indicators, as the significance, relevance and central theme of the interaction came into the focus of our questions, which is most evident in the manifestations of language input and comes from children, as well as infants and young children. The present study focuses on the strategies we encounter in influencing language acquisition in the interaction between children and caregivers.